Estratégias ecológicas com base no sistema LHS (leaf-height-seed) em plantas lenhosas ao longo de gradientes ambientais - Laureto, Livia Maira Orlandi (2012)
How environmental filters and niche differentiation acts in assembly rules and the importance of ecological strategies in such process are unresolved questions in community ecology. We choose a savanna-forest gradient to answer these questions. Such gradient is related with variations in soil fertility, light and disturbance frequency. We used null models and LHS (leafheight-seed) traits, including intraspecific variability, to investigate if niche based process are acting in assemblages along the savanna-forest gradiente. We also investigated if diferente ecological strategies are favored along this gradiente and which edaphic parameters affects niche based process. We found evidence for environmental filtering in forest and savanna assemblages: factors such as soil, light and disturbance affected observed values of functional traits, which were more similar than expected by chance. However, environmental filters selected plants with different trait values along the gradient, highlighting the use of different ecological strategies depending of abiotic characteristics of each assemblage. In forest assemblages competitive strategies were the most commom (higher mean values for the three traits), suggesting that light is a stronger filter than soil nutrient availability. In savanna assemblages smaller plants with smaller specific lead área co-occurred most often, suggesting strategies focused on resource conservation. Furthermore, we found evidence for niche differentiation process (represented by competition between co-occurring plants) only in savanna: trait values were less similar than expected by the null model. Therefore, in such assemblages, where soil fertility is smaller and disturbances are more frequente, niche differentiation acts reducing competition and enabling the permanence of indidividuals in the assemblage. We found, also, that, soil fertility, texture and aluminium-pH are good predictors for both niche based processes. Althought other studies have found evidence for niche based process structuring natural communities, our research provides a more complete investigation about assembly rules, comprising important factors to assemblage dynamics simultaneously such as intraspecific variability, different functional traits and the influence of specific factors like soil.